Poverty Traps and Human Capital Accumulation - Carlotta Berti Ceroni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
In this paper, we analyze the emergence and persistence of poverty traps and study how wide-spread poverty and the unequal distribution of income can slow down the accumulation process and lead to steady-state equilibria characterized by low aggregate output levels. We define poverty as a state deriving from the lack of adequate skills and associate income inequality with the unequal distribution of education attainments. In this context the goal of our contribution is twofold. First, we show that low asymptotic mobility and persistent income inequality can emerge as a consequence of the fact that the poor require relatively higher returns to increase expenditure on education, so that they devote to education smaller shares of their income that the rich. Second, we critically evaluate our and other related results, in order to shed light on the explanatory power of different sets of assumptions.
Keywords: 330